Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae) - Jamhour, Aiman; Mitrović, Milana; Petrović, Andjeljko; Starý, Petr; Tomanović, Željko (Zootaxa, 2016)
Here we tested Aphidius urticae s. str. host-associated lineages from Microlophium carnosum (Buckton), Amphorophora rubi (Kaltenbach), Macrosiphum funestum (Macchiati) and Aulacorthum vaccinii Hille Ris Lambers with the barcoding region of the mitochondrial cytochrome oxidase subunit I gene used to analyse population differences and elucidate phylogenetic relationships between the separated taxa. This molecular marker has been shown to be the most informative molecular marker in resolving species complexes in aphidiine parasitoids. Analyses of the mitochondrial sequences revealed the existence of three clearly separated mitochondrial lineages of A. urticae s. str. group associated with: i) Macrosiphum funestum and Aulacorthum vaccinii aphid hosts, ii) Microlophium carnosum and iii) Amphorophora rubi. This corresponds to the initial descriptions of A. rubi, A. silvaticus and A. urticae and their aphid host associations prior to synonymization of A. rubi and A. silvaticus with A. urticae. On the other hand, significant evolutionary distances ranging from 2.3 to 9.2% between the three mitochondrial lineages were not accompanied by clear morphological differences. Therefore, re-descriptions of A. rubi and A. silvaticus are presented, together with their morphological differentiation in a key, as well as their phylogenetic relationships and genetical differentiation.
Keywords: taxonomické DNA čárové kódování; sršňovití; DNA Barcoding, Taxonomic; druhová specificita; Phylogeny; Female; zvířata; mšice; Mitochondrial Proteins; mitochondriální proteiny; Wasps; ženské pohlaví; respirační komplex IV; Male; fylogeneze; Species Specificity; Electron Transport Complex IV; Animals; mužské pohlaví; Aphids